PERLAKUAN AKUNTANSI KREDIT BERMASALAH (NON PERFORMING LOAN) SERTA KESESUAIANNYA DENGAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN PSAK NO. 71 PADA PT. BANK RAKYAT INDONESIA (BRI) KOTA JAYAPURA KANTOR CABANG ABEPURA - Hary Darmawan; Paulus Allo Layuk; Kurniawan Patma (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2021)
This type of research is a qualitative descriptive comparative study which compares the accounting treatment used by Bank Rakyat Indonesia with PSAK No. 71 on non-performing loans. Based on research conducted at PT. Bank Rakyat Indonesia (Persero). Tbk. Jayapura City Abepura Branch Office to find out the accounting treatment for non-performing loans (non-performing loans) in accordance with PSAK No. 71. It is found that the accounting treatment applied by Bank Rakyat Indonesia for non-performing loans is in accordance with PSAK No. 71 where the credit has been using the method of calculating and providing reserves for losses due to bad loans using the expected loss approach, so that in the event of losses or inflation they can still be taken into account. The accounting treatment in terms of allowance for impairment losses that has been carried out by Bank Rakyat Indonesia, both in lending and lending activities and in impairment activities and write-offs of income from non-performing loans is in accordance with the provisions of PSAK Number 71.